Oferta y demanda de los recursos turísticos Reserva Forestal Protectora Cerro Quininí (Tibacuy- Cundinamarca) - Castellanos Menjura, Claudia Patricia; Ariza Cortés, William; Castrillón Cardona, William Fernando (Revista Científica, 2019)
Tourist resources were evaluated and tourist demand was characterized in the areas of public use of the Cerro Quininí Protective Forest Reserve (RFPCQ), in the Sumapaz region (Tibacuy -Cundinamarca-Colombia), in order to present a diagnosis of tourism activity in the area and become the input for the planning and implementation of a management plan for tourism. The methodology for the evaluation of the offer in relation to tourism management was carried out through interviews, walks and workshops with local experts and the community of the area. Information was obtained for the identification and classification of biophysical, cultural and tourism resources. archaeological On the other hand, the demand for these resources was evaluated with the application of a survey to obtain the profile of the visitors whose data were analyzed by means of the Multiple Correspondence Analysis technique that presented information on trends and preferences. The correlation between the supply of resources and demand was articulated in a SWOT analysis that allows decision-making regarding tourism as a conservation and protection strategy in the study area. With the results, the diagnosis of the tourist supply and demand is obtained, which serves as the basis for the design of the tourism management plan oriented to the needs and conservation of the RFPCQ.